Validity of verbal autopsy for ascertaining the causes of stillbirth - Arun K Aggarwal; Vanita Jain; Rajesh Kumar (The World Health Organization, 2011)
OBJECTIVE: To validate the verbal autopsy tool for stillbirths of the World Health Organization (WHO) by using hospital diagnosis of the underlying cause of stillbirth (the gold standard) and to compare the fraction of stillbirths attributed to various specific causes through hospital assessment versus verbal autopsy. METHODS: In a hospital in Chandigarh, we prospectively studied all stillbirths occurring from 15 April 2006 to 31 March 2008 whose cause was diagnosed within 2 days. All mothers had to be at least 24 weeks pregnant and live within 100 km of the hospital. For verbal autopsy, field workers visited mothers 4 to 6 weeks after the stillbirth. Autopsy results were reviewed by two independent obstetricians and disagreements were resolved by engaging a third expert. Causes of stillbirths as determined by hospital assessment and verbal autopsy were compared in frequency. FINDINGS: Hospital assessment and verbal autopsy yielded the same top five underlying causes of stillbirth: pregnancy-induced hypertension (30%), antepartum haemorrhage (16%), underlying maternal illness (12%), congenital malformations (12%) and obstetric complications (10%). Overall diagnostic accuracy of verbal autopsy diagnosis versus hospital-based diagnosis for all five top causes of stillbirth was 64%. The areas under the receiver operator characteristic curve (ROC) were, for congenital malformations, 0.91 (95% confidence interval, CI: 0.83-0.97); pre-gestational maternal illness, 0.75 (95% CI: 0.65-0.84); pregnancy-induced hypertension, 0.76 (95% CI: 0.69-0.81); antepartum haemorrhage, 0.76 (95% CI: 0.67-0.84) and obstetric complication, 0.82 (95% CI: 0.71-0.93). CONCLUSION: The WHO verbal autopsy tool for stillbirth can provide reasonably good estimates of common underlying causes of stillbirth in resource-limited settings where a medically certified cause of stillbirth may not be available.